Comparison of the Cytotoxic Effects of Nanosilver and Ancient Iranian and Pakistani Silver Kushtas on Primary Rat Hepatocytes and Human Cancer Cell Lines: Comparison of Cytotoxic Effects of Nanosilver and Ancient Iranian and Pakistani Silver Kushtas - Alireza Mozaffari Dehshiri; Mahmoud Mosaddegh; Maryam Hamzelou Moghaddam; Farzaneh Naghibi; Soheila Honary (Iranian Journal of Pharmaceutical Sciences, 2014)
Tumor growth is characterized by uncontrolled cell division. For centuries, silver kushta powder, composed of nano and submicro silver particles, has been used in traditional Iranian and Pakistani medicine for the treatment of melanoma and breast cancer. We have found that these nanocomposite particles are similar to silver nanoparticles (AgNps) in size and shape and that there are so differences in their physicochemical properties such as silver content.In the present study, a comparison of cytotoxic effects of nanosilver(AgNps) and two silver kushtas [Iranian silver kushta (IKAg) and Pakistan silver kushta (PKAg)]have been conductedindifferent concentrations against tumor cell lines (MCF-7, HepG2, A549) and a normal cell line (MDBK) using MTT andTrypan blue exclusion tests.At first, Particle size was analyzed using the Malvern Zetasizer. The Z average diameters of samples (AgNps, PKAg, and IKAg) were64.08, 51.72 and 190.4 nm, respectively.The result of MTTtest showed no toxicity of both silver kushtas (IKAg&PKAg) toward the cancer cell lines and MDBK cells. The IC50 values of AgNpsdetermined for A549, HPG2, MCF-7, and MDBK were 5.94, 1.41, 3.68, and, 1.9 ppm, respectively. According to trypan blue (0.2% w/v) exclusion test, the cytotoxicity of the silver materials toward primary rat hepatocytes followed the order AgNps (100%) >AgNO3 (80.9%) >Pakistani silver kushta (48.35%)>Iranian silver kushta (45%).This result illustrated that the silver components [(IKAg) & (PKAg)] of the traditional kushtas do not penetrate the cancer cell membrane and do not show cytotoxicity. Therefore, kushtas are ineffective as anti-cancer agents. However, AgNps shows good anticancer properties.